2002
DOI: 10.1021/jp0139787
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ XANES of Carbon-Supported Pt−Ru Anode Electrocatalyst for Reformate-Air Polymer Electrolyte Fuel Cells

Abstract: In-situ X-ray absorption near-edge structure (XANES) experiments were performed on a working reformateair fuel cell to study the structure of carbon supported Pt-Ru anode electro-catalyst. The fuel cell was operated in a normal mode without the use of supplemental electrolytes. A fresh membrane electrode assembly (MEA) and a conditioned MEA were studied at different operating conditions of the fuel cell and different feed (pure H 2 or H 2 /CO [100 ppm CO]) at the anode. The in-situ Pt L III -edge and Ru K-edge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(103 citation statements)
references
References 40 publications
6
97
0
Order By: Relevance
“…It is important, however, to bear in mind that this is not necessarily true under the operating conditions used. In fact, several studies have reported that, under typical anode operating conditions, the PtRu catalyst is converted into its metallic state and is possibly present in an alloyed state [47,51], at least as long as the catalyst is not deactivated [52]. Finally, it should be noted that the Ru LIII-edge XANES spectrum of a pure Ru catalyst, of comparable particle size, which is also shown in Figure 5, shows a significantly lower white line intensity, indicating that the Ru LIII-edge is also somewhat affected by the presence of Pt.…”
Section: Original Research Papermentioning
confidence: 99%
See 1 more Smart Citation
“…It is important, however, to bear in mind that this is not necessarily true under the operating conditions used. In fact, several studies have reported that, under typical anode operating conditions, the PtRu catalyst is converted into its metallic state and is possibly present in an alloyed state [47,51], at least as long as the catalyst is not deactivated [52]. Finally, it should be noted that the Ru LIII-edge XANES spectrum of a pure Ru catalyst, of comparable particle size, which is also shown in Figure 5, shows a significantly lower white line intensity, indicating that the Ru LIII-edge is also somewhat affected by the presence of Pt.…”
Section: Original Research Papermentioning
confidence: 99%
“…This will be discussed in more detail below. [47,51], the PtRu/C alloy catalyst electrode also exhibits Pt and Ru surface atoms under reaction conditions. Hence, it should equally exhibit two characteristic peaks for the oxidation of CO adsorbed on Pt and Ru atoms.…”
Section: Original Research Papermentioning
confidence: 99%
“…(ii) Hydrous RuO 2 may be partially reduced to metallic ruthenium. There is evidence that ruthenium oxides can be reduced to metallic ruthenium under the conditions used for CO adsorption [11,28,29]. Since CO is able to adsorb on metallic platinum as well as metallic ruthenium sites, the reduction of RuO 2 would lead to the formation of new CO adsorption sites as long as no free platinum surface is lost during this process.…”
Section: Co-strippingmentioning
confidence: 99%
“…When it comes to methanol electrooxidation, there is no agreement about the oxidation state of Ru existing in PtRu system and conditions for the most active electrocatalytic performance. It has been suggested that Ru may exist either in a form of Ru oxo species [36,37] or metallic Ru [38][39][40][41][42]. Of course, metallic Ru sites must be covered by some oxygencontaining surface groups (e.g., -OH) to act effectively in the bi-functional mechanism.…”
Section: Xps Studymentioning
confidence: 99%
“…In the present work, we have elucidated the influence of supports composed of the poly(diallyldimethylammonium chloride)/PDDA functionalized multi-walled carbon nanotubes (MWCNTs) and Keggin-type heteropolymolybdate (phosphododecamolybdate, PMo 12 O 40 3− or PMo 12 ) modifying agent on catalytic activity of the PtRu nanoparticles during electrooxidation of ethanol. With respect to use of PMo 12 , we have referred to numerous examples in the literature [18][19][20][21][22] demonstrating electrocatalytic properties of polyoxometallates.…”
Section: Introductionmentioning
confidence: 99%